2022
DOI: 10.1021/acs.langmuir.1c02672
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Mechanism in Blood-Compatible Polymers Undergoing Phase Separation

Abstract: Interactions involving intermediate water are crucial for the design of novel blood-compatible materials. Herein, we use a combination of atomic force microscopy, quartz crystal microbalance measurements, and soft X-ray emission spectroscopy to investigate the local hydrogen-bonded configuration of water on blood-compatible poly­(2-methoxyethyl acrylate) and non-blood-compatible poly­(n-butyl acrylate) grafted on a gold substrate. We find that the initially incorporated water induces polymer-dependent phase se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…These interacting water molecules are believed to be actively involved in the prevention of platelet adhesion and the adsorption and denaturation of related serum proteins. [ 18–23 ] Compared to the results in previous reports, [ 24,25 ] the exotherm at ≈−40 °C in the cooling scan appeared to reflect the water interacting with methoxy side groups. Those at ≈−25 °C may correspond to water interacting with ether bonds in the main chain and ester groups in the main and side chains (Figure 6b).…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…These interacting water molecules are believed to be actively involved in the prevention of platelet adhesion and the adsorption and denaturation of related serum proteins. [ 18–23 ] Compared to the results in previous reports, [ 24,25 ] the exotherm at ≈−40 °C in the cooling scan appeared to reflect the water interacting with methoxy side groups. Those at ≈−25 °C may correspond to water interacting with ether bonds in the main chain and ester groups in the main and side chains (Figure 6b).…”
Section: Resultsmentioning
confidence: 52%
“…As mentioned in the Introduction, the blood compatibility of polymers correlates with the hydration properties, [19][20][21] which can be evaluated by differential scanning calorimetry (DSC) and water contact angles. The DSC profiles of polymer 1 showed a glass transition temperature (T g ) of −30 °C in the dry state (Figure 6a).…”
Section: Hydration Properties Of Polymermentioning
confidence: 99%
See 2 more Smart Citations
“…9 This indicates that the specific surface area of PMEA, whose outermost surface swells more easily than that of the polymer in the bulk state, increased upon forming microparticles and this promoted hydration. 30,31 Subsequently, differential scanning calorimetry (DSC) measurements of the polymer microparticles were performed under wet conditions. We have previously reported that the PMEA homopolymer and its derivatives form cold-crystallizable water, called intermediate water (IW), at approximately À40 1C, which plays a key role in the blood compatibility of polymer surfaces.…”
Section: Materials Advances Papermentioning
confidence: 99%